3D mobile map visualization concept for remote rendered dataset - Abubakar, Adamu; Zeki, Akram M.; Haruna, Chiroma (2013)
Three-dimension (3D) maps visualization concept for mobile devices which can be used for navigation aid comes in to being as a result of the weakness perceived with the two dimension(2D) map. The representation of scene in 2D map is generally limited and lack interaction with the users. The interaction of 2D map is limited to the interpretation of symbols explained in the legend which not every user knows how to use efficiently. 3D map, on the other hand, is able to produce a realistic scene. 3D map delivered to mobile device through remote rendering will serves as a navigation aid. Unfortunately, visualization of 3D map in mobile devices is faced with a huge drawbacks when considering the small screen size mobile device and with low computing resources. This paper survey the optimum remote rendered techniques used for 3D visualization on mobile devices and provide a prototype of 3D mobile map that will be suitable as navigation aid. The 3D map that this paper is considering is different from the manipulated static aerial photo-realistic images that gives the illusion of 3D presentation.